HUBUNGAN POLA TIDUR DENGAN KECEMASAN IBU HAMIL DI WILAYAH KERJA BLUD UPTD PUSKESMAS ATARI JAYA - nurlaela, nurlaela; Fitriyanti, Fitriyanti; Elyasari, Elyasari; Kartini, Kartini (Jurnal Stunting Pesisir dan Aplikasinya, 2025)
Introduction: Pregnancy is a natural biological process that is crucial in a woman's life. During this time, women face various challenges, ranging from drastic physical changes, hormonal fluctuations, the responsibilities of being a mother-to-be, to concerns about fetal safety and the delivery process. The purpose of this study was to determine the relationship between sleep patterns and anxiety among pregnant women in the BLUD UPTD Atari Jaya Community Health Center (Puskesmas Atari Jaya) work area. Methods: This study was quantitative and designed using an observational cross-sectional approach. The population was 139 pregnant women at the UPTD Atari Jaya Community Health Center. The sample was 58 pregnant women at the Obstetrics Polyclinic within the UPTD Atari Jaya Community Health Center. The chi-square test was used in the bivariate analysis. Results: Of the 58 respondents, the sleep patterns of pregnant women were mostly in the good category (27 respondents (46.6%). Of the 58 respondents, the anxiety of pregnant women was mostly in the not anxious category (30 respondents (51.7%). The data analysis results obtained an X2 value of 15.237 (greater than the X2 table value of 12.592) and a p-value of 0.018 (? 0.05). Therefore, it can be concluded that there is a relationship between sleep patterns and anxiety among pregnant women in the BLUD UPTD Atari Jaya Health Center Work Area. Conclusion: There is a relationship between sleep patterns and anxiety among pregnant women in the BLUD UPTD Atari Jaya Health Center Work Area.